Regional estimation of sediment yield using monthly sediment rating curve in Qarasu watershed - fariba Esfandiary Darabad; Morteza Gharachorlu (تحقیقات کاربردی علوم جغرافیایی)
This study was aimed at identification and determination the spatial variations of sediment yield in Qarasu watershed located in Ardebil province, NW Iran, considering the negative consequences of erosion and sediment yield. In this regard, the monthly time scale, as the basis of work, was used to prepare the sediment rating curves. Preparation of monthly sediment rating curves based on sample flow and corresponding sediment discharge data in 19 hydrometry stations at the watershed during 14 years (2002-2015). All of statistical analyses were done by SPSS statistical software. Also, presentation of spatial variations in sediment yield over the watershed were made possible through the capability of GIS. The results of regression relations between flow and sediment discharge showed a close and significant relationship on a monthly time scale. The regional generalization of these relations for the whole basin showed that the seasonal difference was evident and the highest and lowest coefficient of determination was allocated to May (R2 = 0.74) and August (R2 = 0.55), respectively. Also, the highest and lowest sediment transport was observed in spring and summer, respectively, indicating the type of rainfall-runoff regime dominated on Qarasu watershed. In terms of the annual sediment yield, Yamchi station with 3970 tons per year and Nanakaran station with 66 tons per year, have the highest and lowest sediment yield among 19 stations of Qarasu watershed, respectively. According to the high levels of sediment yield in the Balikhly and Khyav sub-watersheds, it was recommended that more attention be paid to protecting and strengthening the water and soil elements and reducing the driven forces of erosion and sediment production in these sub-watersheds.